2012
DOI: 10.1039/c2nr31271a
|View full text |Cite
|
Sign up to set email alerts
|

Protein-templated gold nanoclusters: size dependent inversion of fluorescence emission in the presence of molecular oxygen

Abstract: Gold nanoclusters are promising candidates as biological markers without having toxic effects like fluorescent quantum dots. Herein, bovine serum albumin (BSA) protein stabilized gold nanoclusters of two different sizes emitting at 410 and 645 nm have been synthesized. These nanoclusters have been shown to interact with molecular oxygen differentially. Spectroscopic and chemical evidences show that dioxygen molecule gets adsorbed at two different orientations on the nanoclusters. The orientation motifs have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 60 publications
(121 reference statements)
6
42
1
Order By: Relevance
“…The average particle size was found to be around 8 nm (Figure 2) with a narrow size distribution supporting the possibility of the presence of at least two BSA molecules holding gold cluster together. This observation is in well agreement with the report from Purkayastha et al 20 .…”
Section: Resultssupporting
confidence: 94%
“…The average particle size was found to be around 8 nm (Figure 2) with a narrow size distribution supporting the possibility of the presence of at least two BSA molecules holding gold cluster together. This observation is in well agreement with the report from Purkayastha et al 20 .…”
Section: Resultssupporting
confidence: 94%
“…The papers that reported synthesis using NaOH as a reducing agent [13,39] attribute a PL band around 470 nm to the PL of protein. Moreover, using mass spectroscopy Das et al demonstrated that performing the synthesis of BSA-Au NCs using NaOH as a reducing agent, only Au 25 nanoclusters were formed [40]. Both Au 8 and Au 25 nanoclusters were formed when a different reducing agent (ascorbic acid) was used.…”
Section: Discussionmentioning
confidence: 99%
“…640 nm emission) was Au 25 NC (Figures 2c and 2d). 12a (Note: the “blue species” may alternatively be assigned to the oxidized product of Trp from BSA 15…”
Section: Protein‐directed Approachesmentioning
confidence: 99%